Effect of Fluid Velocity and Sand Flowrate on The Intrusive Erosion Probe Using 3D Computational Method - Rosnizam, Nur Izzah Farzana (IRC, 2021)
Sand erosion probe plays a major role in determining the erosion rate of an oil pipeline. Erosions and wear of equipment in oil pipeline is caused by the sand production in oil wells. Sand erosion probe is used to measure the erosion rate of the pipeline.